2002
DOI: 10.1029/2001wr000895
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase advection and dispersion in unsaturated porous media

Abstract: [1] Gas phase miscible displacement experiments were conducted to quantitatively investigate the advective and dispersive contributions to gas phase transport in unsaturated porous media over a range of soil water contents. Furthermore, the independence of measured dispersivity values was evaluated through comparison of nonreactive and reactive tracer transport. Methane was used as a nonreactive tracer, while difluoromethane (DFM) and trichloroethene (TCE) were used as reactive tracers. At soil water contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 47 publications
(51 reference statements)
2
30
0
1
Order By: Relevance
“…Thus, higher soil-water content could lead to a lower k a /e value ( Fig. 9) and probably also to higher a values (Costanza-Robinson and Brusseau, 2002). This could partly explain the relatively high D disp /D 0 values of a Vielsalm samples at low values of k a /e, which exceed the modeled values (Fig.…”
Section: Laboratory Experimentsmentioning
confidence: 49%
See 2 more Smart Citations
“…Thus, higher soil-water content could lead to a lower k a /e value ( Fig. 9) and probably also to higher a values (Costanza-Robinson and Brusseau, 2002). This could partly explain the relatively high D disp /D 0 values of a Vielsalm samples at low values of k a /e, which exceed the modeled values (Fig.…”
Section: Laboratory Experimentsmentioning
confidence: 49%
“…The phenomenon of dispersion is well-known, for example, from contaminant transport in ground water (Delgado, 2006), but is also relevant in the gas phase of porous media (Scotter and Raats, 1969;Costanza-Robinson and Brusseau, 2002).…”
Section: Turbulence-driven Pressure Pumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that mechanical dispersion dominates over molecular diffusion for higher gas flow velocities through porous materials. [25][26][27][28] Gidda et al. 27 also suggest that the gas dispersivity increases for materials with a wider particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…を求めた. また,分散長に関しては,ガス流速の遅い範囲では,前 記のHibi et al 16) とCostanza-Robinson and Brusseau 6) ,ガス流速 が早い範囲についてはGidda et al 18) が一次元カラム実験を 用いて分散長を求めている.Costanza-Robinson and Brusseau 6) とGidda et al 18) は,Fickの法則に従って機械分散係数 および分散長を求めたが,Hibi et al 16) はDusty gasモデルを 加味して機械分散係数について検討した. 以上のように,屈曲度を考慮した分子拡散係数,拡散 係数に関係する屈曲度,Knudsen拡散係数,機械的分散 係数を個別または一部同時に求める試みがなされている が,一次元カラム実験を用いて,同時にこれらのパラメ ーターを求める手法は,著者が調べた範囲では開発され ていない.なお,ここで言う機械的分散係数とは,土粒 子により生じる間隙中のガスの流れの経路と分岐により 汚染物質が拡がる現象,または間隙中の土粒子とガスの 境界におけるガス流速と,間隙中のガスが流れる経路中 央におけるガス流速の違いにより生じる現象のことであ る.本研究では,2成分のDusty Gas モデルにより乾燥土 の一次元カラム実験結果からこれらのパラメーターを求 める手法を開発し,実際の実験結果からこの手法を用い て前記の各パラメーターを求めることができることを確 認した. 2. 分散係数とKnudsen拡散係数の算出方法 後述するように,今回の実験では水平方向の一次元カ ラム実験を行っているので,重力による影響を無視する ことができる.重力による影響を無視した土中ガス中の 2成分のDusrty Gas Modelは,Abriola et al 19) ,Hibi 20) ,Hibi et al 21) ,Webb and Pruess [198][199][200][201][202][203][204][205][206][207][208][209]2011.…”
Section: )unclassified